Electrochemical Generation of Porphyrin-Porphyrin and Porphyrin-C60 Polymeric Photoactive Organic Heterojunctions - Suárez Ramanzin, Maria Belen (2014)
Photoactive organic-organic interfaces are formed by electrochemical synthesis. The generation of porphyrin/porphyrin and porphyrin/C60 heterojunctions over indium tin oxide electrodes by successive electropolymerization steps is described. Functionalized C60 buckminsterfullerene holding a carbazol residue and porphyrins containing carbazol and phenylamino moieties are able to form electrodeposited layers by cyclic voltammetry. Photoinduced electron transfer between Zn(II), free base porphyrins and C60 films were analyzed by both, light modulated surface photovoltage spectroscopy and laser induced transient photovoltage. The results showed that the electrochemical generated polymeric heterojunctions are able to produce photoinduced charge separated states, which could present a potential application in the design and construction of organic optoelectronic devices.